Discovery Driven Innovation: The Case of Oman Entrepreneurship - Matriano, Maria Teresa (Advances in Social Sciences Research Journal, 2019)
Businesses around the world fail or succeed because decisions good or bad were made out of assumptions of the unknown. In the context of discovery-driven innovation, business decision can be made with the aid of available information based from passed attempts, the current market situation, and consumer dynamics. The discussion involves examining the importance of discovery-driven innovation in business growth. Oman ha a young SME sector in which several entrepreneurs succeed and failed due to a common cause, which is the lack of drive to discover what works for their business and the lack of innovation applied to their operational strategies. Discovery-driven innovation in the case of Oman encompasses the limitations faced by entrepreneurs in reinventing their business ideas based from data about the past and existing enterprises. In discovering what works, what did not work, and why it didn’t, entrepreneurs would be able to make evidence- based decision that can assist them in innovating the way they do business. Keywords: Commercialization, Consumer Market, New Products, Business Process/strategies